Structure Evolution and Palinspastic Analysis of The Gurami-Tamiang Area, North Sumatra Basin, Indonesia - Dumex Pasaribu; Benyamin Sapiie; Indra Gunawan (Testing Center for Oil and Gas LEMIGAS, 2025)
The Sumatran back-arc basins developed beginning in the Middle Eocene, characterized by a variety of graben alignment patterns, which serve as critical indicators in understanding their formation history. One such basin is the North Sumatra Basin, dominated by north-south-trending grabens. These grabens are best observed in the Gurami-Tamiang Area. This research focuses on the subsurface analysis of this area, specifically: (i) detailed seismic interpretation of four east-west cross-sections that span several grabens, and (ii) palinspastic reconstructions to investigate structural and strain evolution over time, and its tectonochronostratigraphic chart. Generally, the structural configuration of the Gurami-Tamiang Area is defined by half-grabens bounded by east-dipping faults originating from negative flower structures at depth. The results show three phases of evolution: (i) Extensional Phase (45 - 32 Ma) is characterized by growth strata and strain magnitudes of (+) 4.2% to (+) 11.64%, (ii) Transitional Phase (32 - 22 Ma) is displaying both positive and negative strains of (+) 2.3% to (-) 1.7%, with growth strata that are extending across grabens; and (iii) Contractional Phase (22 Ma – present) is characterized by negative strains of (-) 0.92% toward zero and mostly covered by post-extensional and syn-inversion deposits. The evolutionary phases indicate a novelty in the area, with the graben formation being part of a wrench fault system that includes the Khlong-Marui Fault, the Lokop-Kutacane Fault, and the Sumatra Fault.